Het Portret 1965-1985. - van Ruysbeek, Erik; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1988)
Burssens, Jan ; Crommelynck, Albert ; De Boeck, Felix ; Elias, Etienne ; Jans, Jos ; Landuyt, Octave ; Minnaert, Frans ; Raveel, Roger ; Roobjee, Pjeroo ; Somville, Roger ; Szymkowicz, Charles ; Theys, Yvan ; Vanriet, Jan ; Van Tuerenhout, Jef ; Vervisch, Godfried
Het Portret 1965-1985, Hof ter Nederloo, Sint-Pieters-Leeuw, 28 februari - 20 april 1986
boek